(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Taisiya I. Skorobogatova, Elena A. Manaenko (Rostov-on-Don, Russian Federation) In the article on a material of modern French language the main sources of origin of phraseology-quotes are considered. The authors propose to understand by the term «idiom-quote» such idioms, derivation base of which is a verbatim excerpt from some text (poetry, prose, song, or creolized texts, in particular, advertising texts, comics, etc.), as well as utterances of characters of art and animation films, the sayings of prominent representatives of the various spheres of human activity. Idiom-quote to a certain extent can be associated with the source of language native origin, provided it is wide distributed and widely employed. Idiom-quote occupies an intermediate position in a row: catchphrase> idiom-quote> phraseological unit. Those idioms, quotations, which after a special etymological analysis and consolidation of different phrasebook refer to some sources quoted gradually make the transition into the category of phraseology, thereby ceasing to be exclusively a fact of culture and becoming a fact of language. Key words: idiom, quote, quotation phraseology, phraseological unit, phraseology, sayings, quote, French.